SARS-CoV-2's high rate of genetic mutation under immune selective pressure: from oropharyngeal B.1.1.7 to intrapulmonary B.1.533 in a vaccinated patient. (May 2022) - Musso, Nicolò; Maugeri, Jessica Giuseppina; Bongiorno, Dafne; Stracquadanio, Stefano; Bartoloni, Giovanni; Stefani, Stefania; Di Stefano, Emanuela Daniela
Highlights: It could be useful to know the infection status before SARS-CoV-2 vaccination. SARS-CoV-2 virus can mutate inside the human host. SARS-CoV-2 virus tends to change under selective pressure. Abstract: This is the case report of an 84-year-old man affected by COVID-19 between the 2 doses of vaccination, with negative exitus. We analyzed nasopharyngeal samples of viral RNA collected during the disease and nasopharyngeal and lung samples collected postmortem by reverse transcription LAMP (RT-LAMP) PCR and Next Generation Sequencing (NGS). NGS results were analyzed with different bioinformatic tools to define virus lineages and the related single-nucleotide polymorphisms (SNPs). Both lung and nasopharyngeal samples tested positive for SARS-CoV-2 on RT-LAMP. Through bioinformatic analysis, 2 viral RNAs from the nasal swabs, which belonged to the B.1.1.7 lineage, and 1 viral RNA from the lung sample, which belonged to the B.1.533 lineage, were identified. This genetic observation suggested that SARS-CoV-2 tends to change under selective pressure. The high mutation rate of ORFa1b, containing a replicase gene, was a biological image of a complex viral survival system.